2020
DOI: 10.1101/2020.04.21.050104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A preliminary study on the reproductive toxicity of GS-5734 on male mice

Abstract: Background: GS-5734 as a novel and promising medicine for COVID-2019, its biological impact on the mammalian reproductive system has not been systematically studied. The aim of this study was to evaluate the effects of GS-5734 on sperm parameters and spermatogenesis in mice. Materials and Methods:In this study, GS-5734 was synthesized according to the report. 28 adult male mice were randomly segregated into four groups (n=7 for each group). The group 1 was set as the control group, the group 1, 2, 3 and 4 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This may be suggested that this drug act on male reproductive organ. A study conducted in India showed that the effects of antiviral drug on male reproductive system in rats which showed that another antiviral drug ribavirin act on testes and reduces the number of seminiferous tubules (18) Study conducted on the another antiviral drug which shows that there was formation of vacuoles occur at the Sertoli cell in terms of endoplasmic retinaculum dilatations (18), this suggested that the there must be some non-specific injury of testis occur and a gap in the seminiferous tubules is due to the sloughing of germ cells (18) A study conducted in China supports present study which showed that in high doses remdesivir produces toxicity of male reproductive organ so in high dose it should be used cautiously while in low or intermediate dose it doesn't effect male reproductive organ significantly (16) .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This may be suggested that this drug act on male reproductive organ. A study conducted in India showed that the effects of antiviral drug on male reproductive system in rats which showed that another antiviral drug ribavirin act on testes and reduces the number of seminiferous tubules (18) Study conducted on the another antiviral drug which shows that there was formation of vacuoles occur at the Sertoli cell in terms of endoplasmic retinaculum dilatations (18), this suggested that the there must be some non-specific injury of testis occur and a gap in the seminiferous tubules is due to the sloughing of germ cells (18) A study conducted in China supports present study which showed that in high doses remdesivir produces toxicity of male reproductive organ so in high dose it should be used cautiously while in low or intermediate dose it doesn't effect male reproductive organ significantly (16) .…”
Section: Discussionsupporting
confidence: 62%
“…Remdesivir has shown side effects on gonads. It may cause deterioration of quality of sperm in mice (15) , quality of semen and sperm in rats and also reduction in the development of Sertoli cells, prostate gland and seminal vesicles (16), (17) .…”
Section: Introductionmentioning
confidence: 99%
“…One study found that large doses of remdesivir caused insulin pill toxicity and led to sperm parameter deterioration in mice. Therefore, additional studies on the reproductive toxicity of the drug are needed [ 140 ]. Nevertheless, remdesivir was approved by the FDA as the first COVID-19 treatment drug in the US.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Remdesivir is approved by the FDA for the treatment of COVID-19 in hospitalized adult and pediatric patients ( 70 ). Up to now, there have been no reports of Remdesivir concerning the adverse effect on the human productive system despite one investigation suggesting the reproductive toxicity of Remdesivir, which was withdrawn by the authors for better experimental design ( 71 ). IFN-α is known for antiviral, antiproliferative, and immunoregulatory activities ( 72 ).…”
Section: The Reproductive Toxicity Of Drug Treatment Of Covid-19mentioning
confidence: 99%